2016
DOI: 10.1007/s11427-016-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and annotating human bifunctional RNAs reveals their versatile functions

Abstract: Bifunctional RNAs that possess both protein-coding and noncoding functional properties were less explored and poorly understood. Here we systematically explored the characteristics and functions of such human bifunctional RNAs by integrating tandem mass spectrometry and RNA-seq data. We first constructed a pipeline to identify and annotate bifunctional RNAs, leading to the characterization of 132 high-confidence bifunctional RNAs. Our analyses indicate that bifunctional RNAs may be involved in human embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…Interestingly, 39 newly annotated genes possess both coding and long noncoding transcripts with high confidence, similar to the 231 known genes with this property in Ensembl. Genes such as SRA ( 43 ) and VegT ( 44 ) have both coding and noncoding transcripts which indicates a gene may possess versatile functions ( 45 ). A published RT-PCR experiment confirmed three multi-exon lncRNAs in rat ( Supplementary Figure S3D in ( 28 )), two of which (rnor_lincRNA13804051, rnor_lincRNA4244571) are verified as lncRNAs with high confidence in RTR (RTRG.42653.1 and RTRG.13897.2, respectively); another multi-exon lncRNA (rnor_lincRNA4825071) has earlier been added to Ensembl (ENSRNOT00000085828).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, 39 newly annotated genes possess both coding and long noncoding transcripts with high confidence, similar to the 231 known genes with this property in Ensembl. Genes such as SRA ( 43 ) and VegT ( 44 ) have both coding and noncoding transcripts which indicates a gene may possess versatile functions ( 45 ). A published RT-PCR experiment confirmed three multi-exon lncRNAs in rat ( Supplementary Figure S3D in ( 28 )), two of which (rnor_lincRNA13804051, rnor_lincRNA4244571) are verified as lncRNAs with high confidence in RTR (RTRG.42653.1 and RTRG.13897.2, respectively); another multi-exon lncRNA (rnor_lincRNA4825071) has earlier been added to Ensembl (ENSRNOT00000085828).…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent results from software used for the judgement of coding ability appeared to be the cause. Newly annotated transcripts with ambiguous coding ability may be due to shortcomings of these softwares or because a transcript may act in both coding and noncoding roles ( 45 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…These protocols are extremely useful for sequencing long noncoding RNAs (lncRNAs) and circular RNAs (circRNAs). Lots of studies have demonstrated that lncRNAs and circRNAs play important roles in diverse biological processes of cells and may serve as crucial biomarkers for cancers (Barrett and Salzman, 2016; Chen et al, 2016b; Quinn and Chang, 2016; Kristensen et al, 2018); therefore, such scRNA-seq methods can provide unprecedented opportunities to comprehensively explore the expression dynamics of both protein-coding and noncoding RNAs at the single-cell level.…”
Section: Currently Available Scrna-seq Technologiesmentioning
confidence: 99%
“…Driver genes/alterations, such as MYCN , 1p/11q deletion, ALK, ATRX and TERT , are characterized in high-risk neuroblastoma by previous studies, however, it is difficult to further stratify the high-risk neuroblastoma at molecular level. Previous studies have mostly intended to predict high-risk neuroblastoma survival using only genomic alterations (Stigliani et al, 2012 ) or dysregulated genes (Blanc et al, 2005 ; Chen et al, 2016 ; Wei et al, 2018 ), rarely by multi-omics integration. Therefore, the lack of prognostic stratification for high-risk neuroblastoma by multi-omics data integration motivated us to conduct this study.…”
Section: Introductionmentioning
confidence: 99%